DEVELOPING HIDDEN OBJECT MEDIA FOR TEACHING ENGLISH AT THIRD GRADE ELEMENTARY STUDENTS IN SD LAB UNDIKSHA SINGARAJA - ., Ida Ayu Putu Putri Gita Sari; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Ni Wayan Surya Mahayanti, S.Pd.,M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk (1) mengembangkan ‘Hidden Object Media’ dalam pembelajaran Bahasa Inggris kelas tiga Sekolah Dasar dan (2) mengetahui kualitas dari penggunaan ‘Hidden Object Media’ untuk pembelajaran Bahasa Inggris kelas tiga di SD Lab Undiksha Singaraja. Subjek dari penelitian ini ialah tiga puluh tujuh siswa kelas III Sekolah Dasar di SD Lab Undiksha Singaraja pada semester genap tahun ajaran 2016/2017. Penelitian ini termasuk dalam jenis penelitian pengembangan yang berdasarkan pada lima prosedur ADDIE oleh Branch (2010) meliputi Analisis, Desain, Pengembangan, Implementasi dan Evaluasi. Dalam pelaksanaanya, penelitian ini menggunakan beberapa instrumen yaitu panduan wawancara, lembar observasi, kuesioner, rubrik dan catatan. Pada akhir penelitian ini, dihasilkan prototipe produk yaitu Hidden Object Media dalam bentuk handout. Hasil dari penelitian ini ialah empat buah Hidden Object Media yang dikembangkan berdasarkan silabus kompetensi, silabus analisis serta karakteristik dari media dengan topik Animals serta Body Parts. Setiap media yang dikembangkan terdiri dari panduan guru, cerita pendek, Hidden Object Handout, dan daftar kegiatan lanjutan yang dapat diterapkan. Dalam hal kualitas media, berdasarkan hasil dari pengujian ahli serta kuesioner guru, Hidden Object Media termasuk dalam kategori media yang sangat bagus. Maka dari itu, media ini cocok digunakan untuk pengajaran Bahasa Inggris kelas tiga Sekolah Dasar. Kata Kunci : hidden object media, handout, pembelajaran Bahasa Inggris untuk anak - anak This research aimed to (1) develop ‘Hidden Object Media’ in teaching English for third-grade of elementary school and (2) investigate the quality of ‘Hidden Object Media’ for teaching English at third-grade elementary students in SD Lab Undiksha Singaraja. The subject of this research was thirty seven of third grade students in SD Lab Undiksha Singaraja at even semester academic year 2016/2017. This research categorized as ‘Research and Development’ (R & D) in which it was following five procedures of ADDIE based on Branch (2010). The five procedures consist of Analyze, Design, Development, Implementation and Evaluation. In executing the procedures, some instruments were used to conduct this research. There was interview guide, observation sheet, item of questionnaire, rubric, and notes. In the end of this research, there was a prototype product named hidden object media which was in a form of handout. The result of this research is four hidden object media that were developed based on syllabus competences, syllabus analysis as well as characteristics of media developed based on two topics which are animals and body parts. Each media consist of teacher’s guidelines, brief story, hidden object handout, and list of possible post activities. In term of quality, based on the result of expert judgment and teacher’s questionnaire it was found that hidden object media were categorized as excellent media. Thus, this media was proper to use for teaching English for third grade students. keyword : hidden object media, handout, teaching English for young Learners